'Just in case': The fertility information needs of teenagers and young adults with cancer2. (20th October 2013) - Wright, C.I.; Coad, J.; Morgan, S.; Stark, D.; Cable, M.
<x xml:space="preserve">Abstract</x> Understanding the reproductive and fertility concerns of teenagers and young adults with cancer (TYA) is one aspect of comprehensive age appropriate care. However, limited options for fertility preservation, coupled with vague policy recommendations, give rise to variations in information‐sharing between health care professionals and TYAs, particularly as it involves sensitive discussions regarding the short‐ and long‐term effects of cancer and treatments on fertility and reproduction. This paper presents findings from a wider evaluation at a specialist unit for TYAs with cancer. Forty people participated in semi‐structured interviews, including 20 young people, parents and partners. Young people were between 2 months and 4 years from finishing treatment. Most young people received mixed levels of information on fertility and counselling before treatment. Diagnosis in the early teens meant how, and from whom, young people received information varied. Young women tended to receive incomplete information. The majority of young people were unaware of their fertility status after treatment had finished. Findings point to the inherent challenges that exist in ensuring young people aged between 13 and 25 years receive comprehensive information on their fertility and potential risk, as well as advice on how to determine their fertility status after treatment has finished.